ETHNOMATHEMATICS: EXPLORATION OF MATHEMATICS THROUGH A VARIETY OF BANTEN BATIK MOTIFS - Citra Elvina Sianturi; Elga Sandi Kiawati; Eva Cahya Ningsih; Neria Ros Fitria; Nila Nurjanah; Jaka Wijaya Kusuma (International Journal of Economy, Education and Entrepreneurship, 2022)
Mathematics is a science interconnected with human life, one of which is the field of culture. The relationship between culture and mathematics is referred to as ethnomathematics. Ethnomathematics is a study of science that studies the relationship of mathematics to culture. Indonesia has a cultural diversity, one of which is batik. Which batik has been designated as a cultural heritage by UNESCO and should be developed and preserved by the community? Batik Indonesia has motifs and patterns according to their respective regions. Banten as a batik producing area has 75 varieties of Banten batik motifs that were legitimized on May 25, 2004. This study describes several Batik motifs and their relation to mathematical concepts. The research was conducted using a qualitative descriptive method with an ethnographic approach. This study found that the variety of Banten batik motifs has mathematical and philosophical value. The mathematical value contained in the Banten batik motif is in mathematical concepts consisting of plane figures and geometric transformation